2021
DOI: 10.3389/fphar.2021.727771
|View full text |Cite
|
Sign up to set email alerts
|

Is Targeting Nerve Growth Factor Antagonist a New Option for Pharmacologic Treatment of Low Back Pain? A Supplemental Network Meta-Analysis of the American College of Physicians Guidelines

Abstract: Objective: It has been found that targeting nerve growth factor antagonists (ANGF) have excellent effects in the treatment of chronic pain, and the current pharmacologic treatments have very limited effects on low back pain (LBP). Thus we conducted this network meta-analysis (NMA) to study the efficacy and safety of ANGF for the treatment of LBP, and to guide for clinical practice and further research.Method: PubMed, Scopus, Embase, CNKI, and the Cochrane Library were searched from January 1980 to March 2021. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…However, current preclinical LBP models are relatively limited, with most of them examining discogenic pathologies [ 16 , 17 ], despite muscle being identified as a common source of LBP [ 3 , 16 , 17 , 18 ]. Importantly, regardless of the etiology of LBP, there appears to be an increasing clinical interest in the role that nerve growth factor (NGF) plays, as anti-NGF approaches in recent LBP clinical trials demonstrated efficacy in the management of LBP [ 19 , 20 , 21 ]. Therefore, preclinical models that mimic the clinical features of LBP become of great importance for the development of novel pharmacological and nonpharmacological strategies to effectively treat LBP.…”
Section: Introductionmentioning
confidence: 99%
“…However, current preclinical LBP models are relatively limited, with most of them examining discogenic pathologies [ 16 , 17 ], despite muscle being identified as a common source of LBP [ 3 , 16 , 17 , 18 ]. Importantly, regardless of the etiology of LBP, there appears to be an increasing clinical interest in the role that nerve growth factor (NGF) plays, as anti-NGF approaches in recent LBP clinical trials demonstrated efficacy in the management of LBP [ 19 , 20 , 21 ]. Therefore, preclinical models that mimic the clinical features of LBP become of great importance for the development of novel pharmacological and nonpharmacological strategies to effectively treat LBP.…”
Section: Introductionmentioning
confidence: 99%